The Relationship Between Internality and Self-Development of Psychology Students: The Effect of Optimistic Attributional Style - Ketler-Mytnytska, Tetiana; Shevchenko, Nataliia (Social Welfare: Interdisciplinary Approach, 2023)
The article representes the research of relationship between internality and self-development in case of different optimistic attributional styles’ levels. The sample consists of psychology students of Ukraine. The strong positive impact of internality on self-development under conditions of medium optimistic attribution has been revealed. It also has been set a decrease in self-development of psychology students with high internality in case of a highly developed optimistic attributional style. It has been established that the highest scores of self-development have psychology students with a medium level of optimistic attributional style and a high level of internality. The lowest self-development is typical of psychology students with high internality and pessimistic attributional style.
Keywords: self-development; internality; optimistic attributional style; optimism; psychology students